A new, remarkable species of Platystethynium (Platypatasson) (Hymenoptera: Mymaridae) from New Zealand - Huber, John T.; Read, Jennifer (Zootaxa, 2021)
Platystethynium (Platypatasson) earlyi Huber, sp. n. (Hymenoptera: Mymaridae), is described from both sexes reared from an egg of Rhaphidophoridae (Orthoptera) found in an old mining tunnel in New Zealand. The male is micropterous and has lateral ocelli but no median ocellus, a unique feature in Mymaridae found so far only in males of Platystethynium Ogloblin species. The remaining described Eastern Hemisphere species of Platystethynium are discussed and Platystethynium glabrum Jin & Li, syn. n., is placed in synonymy under P. onomarchicidum Ogloblin. A key to females, and males where known, of the described Eastern Hemisphere species of Platystethynium is given.